Effect of Business Climate on Entrepreneurial Behavior and Its Implications for Performance in Culinary Micro Enterprises, Serang Regency - Trihana Kurniawati; Muhammad Suparmoko; Uli Wildan Nuryanto; Bambang Dwi Suseno; Basrowi Basrowi (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
The purpose of this research is to analyze effect of business climate on entrepreneurial behavior and its implications for performance in Culinary Micro Enterprises, Serang Regency. This research is a quantitative descriptive research. Population in this study is Culinary Micro Enterprises entrepreneurs, Serang Regency, Banten Province. Sampling technique in this study is to use a saturated sampling technique. Sample of this research is 100 Culinary Micro Enterprises entrepreneurs, Serang Regency, Banten Province. Data analysis using structural equation modeling (SEM). The results of the study show that business climate has no significant effect on entrepreneurial behavior in Culinary Micro Enterprises, Serang Regency. Business climate has no significant effect on performance in Culinary Micro Enterprises, Serang Regency. Entrepreneurial behavior has a significant effect on performance in Culinary Micro Enterprises, Serang Regency. Business climate has no significant effect on performance through entrepreneurial behavior in Culinary Micro Enterprises, Serang Regency.